rice acyl-CoA-binding protein gene family: phylogeny, expression and functional analysis - Meng, Wei; Su, Yvonne C.F; Saunders, Richard M.K; Chye, Mee-Len (The New phytologist, 2011)
• Acyl-CoA-binding proteins (ACBPs) show conservation in an acyl-CoA-binding domain (ACB domain) which binds acyl-CoA esters. Previous studies on plant ACBPs focused on eudicots, Arabidopsis and Brassica. Here, we report on the phylogeny and characterization of the ACBP family from the monocot Oryza sativa (rice). • Phylogenetic analyses were conducted using 16 plant genomes. Expression profiles of rice ACBPs under normal growth, as well as biotic and abiotic stress conditions, were examined by quantitative real-time reverse-transcription polymerase chain reactions. In vitro acyl-CoA-binding assays were conducted using recombinant (His)₆-tagged ACBPs. • The ACBP family diversified as land plants evolved. Classes I and IV show lineage-specific gene expansion. Classes II and III are closely related phylogenetically. As in the eudicot Arabidopsis, six genes (designated OsACBP1 to OsACBP6) encode rice ACBPs, but their distribution into various classes differed from Arabidopsis. Rice ACBP mRNAs showed ubiquitous expression and OsACBP4, OsACBP5 and OsACBP6 were stress-responsive. All recombinant rice ACBPs bind [¹⁴C]linolenoyl-CoA besides having specific substrates. • Phylogeny, gene expression and biochemical analyses suggest that paralogues within and across classes are not redundant proteins. In addition to performing conserved basal functions, multidomain rice ACBPs appear to be associated with stress responses.